1993
DOI: 10.1083/jcb.121.4.811
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of tropomyosin isoform organization and gene expression in response to altered actin gene expression.

Abstract: Abstract. Phenotypically altered C2 myoblast cells, generated by the stable transfection of human nonmuscle actin genes (Schevzov, G., C. Lloyd, and P. Gunning. 1992. J. Cell Biol. 117:775-786), exhibit a differential pattern of tropomyosin cellular organization and isoform gene expression. The/~-actin transfectants displaying a threefold increase in the cell surface area, showed no significant changes in the pattern of organization of the high Mr tropomyosin isoform, Tm 2, or the low Mr tropomyosin isoform, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…This is entirely consistent with previous studies that have shown that Tm isoforms differ in their ability to restore cell shape to transformed cells (Gimona et al, 1996) and in their impact on neuroepithelial cells (Bryce et al, 2003; Figure 6). In addition, the original demonstration that ␤ and ␥-actin carry different structural information (Schevzov et al, 1992) may be accounted for by their differential impact on Tm isoform levels and organization (Schevzov et al, 1993). In all cases, the alterations in cell shape are consistent with changes in the organization of actin filaments.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This is entirely consistent with previous studies that have shown that Tm isoforms differ in their ability to restore cell shape to transformed cells (Gimona et al, 1996) and in their impact on neuroepithelial cells (Bryce et al, 2003; Figure 6). In addition, the original demonstration that ␤ and ␥-actin carry different structural information (Schevzov et al, 1992) may be accounted for by their differential impact on Tm isoform levels and organization (Schevzov et al, 1993). In all cases, the alterations in cell shape are consistent with changes in the organization of actin filaments.…”
mentioning
confidence: 68%
“…Alterations in the expression of actin and tropomyosin by in vitro transfection studies in different cell types have previously been shown to change the expression of other members of these gene families (Schevzov et al, 1993;Bryce et al, 2003). Consequently, we hypothesized that the observed increase in growth cone size seen in Tm5NM1 neurons could be due to changes in the expression and/or subcellular localization of other cytoskeletal proteins.…”
Section: Recruitment Of Tm5a and Myosin Iib By Tm5nm1 To The Growth Conementioning
confidence: 96%
“…Furthermore, TGF␤ enhances contractile activity of SCFs without changing SMMHC or NMMHC expression. Further studies are needed to determine whether enhanced ␣-SMA expression influences other structural proteins that are involved in cell contraction in an isoform-specific manner, such as tropomyosin (Schevzov et al, 1993), caldesmon (Bretscher and Lynch, 1985), calponin (Gimona et al, 1992), SM22 (Gimona et al, 1992), and gelsolin (Arora et al, 1999a) or whether it affects regulatory events, including myosin light-chain phosphorylation, small GTPase activation, and calcium signaling (Parizi et al, 2000). The 3ЈUTRs of ␣-cardiac and ␤-cytoplasmic actin have been suggested to facilitate actin isoform sorting in the cytoplasm by localizing to different subcellular compartments (Kislauskis et al, 1993) and the 3ЈUTR of ␣-tropomyosin has been shown to exert functional tumor suppressor activity (Rastinejad et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In zebra fish, a mutation of the TnT2 gene (silent heart, sih) has been found to severely reduce not only TnT expression but also TnI3 and Tm-α (Sehnert et al, 2002), and, in a myoblast cell culture system, a β-actin gene mutation causes reduced protein and mRNA levels of Tm2 and Tm3 (Schevzov et al, 1993). Furthermore, relative mRNA output between contractile gene families in humans has been found at different stages of development, and independently of isoform switching, which suggests the existence of some form of communication between these genes (Wade et al, 1990).…”
Section: Discussionmentioning
confidence: 99%